Incentivizing a Sustainable Clean Cooking Market : Lessons from a Results-Based Financing Pilot in Indonesia - World Bank Group (World Bank, Washington, DC, 2018)
Access to clean cooking solutions remains one of the most daunting development challenges. Based on the latest Global Tracking Framework, the annual access growth rate of 0.46 percentage points did not keep pace with population growth. In fact, the global population without access increased by 2 million annually, reaching 2.98 billion in 2016, which has profound impacts on public health and gender equality, poverty alleviation, environmental quality, and climate change. Because cooking is a highly contextualized system, local innovation and contextualized solutions are critical for long-term sustainability. Incentives or subsidies will be needed to achieve universal access to modern energy cooking solutions. Government policies are needed to (i) establish and maintain adequate levels of subsidy and (ii) design and implement effective subsidy allocation mechanisms to mobilize and sustain private-sector participation in scaling up access to modern cooking solutions and targeting households who have an affordability gap. The pilot experience in Indonesia shows that the results-based financing (RBF) framework can be an effective tool for unifying key elements for developing a sustainable clean cooking market. Development and implementation of the RBF pilot program under the Indonesia Clean Stove Initiative (CSI) confirm that RBF is a replicable and scalable mechanism for using public resources to incentivize the clean stoves market and can be adapted to other country contexts.